The British are coming : the graphic edition. Volume 1 - Atkinson, Rick; Neus, Nora (Atkinson, Rick. Revolution trilogy (Series), 2026)
"This striking graphic edition adapts the first half of the New York Times bestselling The British Are Coming, the opening volume in Pulitzer Prize-winning historian Rick Atkinson's extraordinary trilogy about the American Revolution. From the battles at Lexington and Concord in the spring of 1775 through the Siege of Boston in 1776, American militiamen and the newly created Continental Army take on the world's most formidable adversary: the British Empire. The gripping saga is alive with astonishing characters: Henry Knox, the former bookseller with an uncanny understanding of artillery; Nathanael Greene, the blue-eyed bumpkin who becomes a brilliant battle captain; Benjamin Franklin, the self-made man who proves to be the wiliest of diplomats; and George Washington, the commander in chief who learns the difficult art of leadership when the war seems all but lost. The story is also told from the British perspective, making the mortal conflict between redcoats and rebels all the more compelling. Full of riveting details and iconic stories, The British Are Coming is a tale of heroes and knaves, of sacrifice and blunder, of redemption and profound suffering. Expertly rendered in gripping graphic novel-style artwork, the battle for our nation's independence is brought to life like never before. Discover the first act of America's creation in this vividly illustrated graphic history."--